Análisis del comercio electrónico en las MIPYMES de los cantones Pedernales y Jama de la provincia de Manabí - Mero Moreira, Shirley Jamileth (2023)
The objective of this work was to analyze electronic commerce in MIPYMES of the Pedernales and Jama cantons, Manabí province to identify the factors that influence this activity. Three actions were established, the identification of the factors of electronic commerce that affect MIPYMES, knowing the elements of consumer decision at the time of online transactions and a proposal for improvement for the applicability of electronic commerce. Inductive-deductive, analytical-synthetic and statistical methods were used, which allowed the processing and representation of data from the interview and survey. The most relevant results of the analysis of the macro and micro environment, determined that the main limitations of electronic commerce in the MIPYMES in the cantons indicated are: the little support of the authorities at Decentralized Autonomous Governments at the cantonal level, the scarce knowledge of the owners of the MIPYMES, the lack of resources, applications and technological platforms. While the most relevant decision factors that influence consumers are the security and confidence provided by the website when entering their personal and banking data, so it is concluded that the proposal of an improvement plan allowed the applicability of electronic commerce in MIPYMES successfully, for which three steps were developed: generate presence on the web, automate the E-commerce process and integrate MIPYMES into electronic commerce. Generating efficient operations, better organizational and productive management, achieving the satisfaction of customers, suppliers and employees.